THE EVERYONE IS TEACHER HERE METHOD ON SPEAKING SKILLS IN THE INDONESIAN LANGUAGE SUBJECT OF FIFTH GRADE STUDENTS AT SD NEGERI 03 AUR TAJUNGKANG - Zola Adria Utami Zola; Munjiatun; Sri Suwartini (Yayasan Thaifah Manshurah Pekanbaru, 2023)
This study aims to determine the effect of the Everyone Is Teacher Here method on speaking skills in the Indonesian language subject of fifth grade students at SD Negeri 03 Aur Tajungkang. In this study, the type of pre-experimental research design was used with the type of one group pretest and post-test . Data analysis techniques in this study are descriptive statistical data analysis and inferential statistical data analysis (t-test). Based on the results of the research pretest it is known that the average student is 69.03. After being given treatment by applying the Everyone Is Teacher Here method , the results of the research post-test experienced an increase with the average student being 89.68. Based on the results of the analysis using the t-test formula, t count is 6.188 and t table is 2.039 meaning t count > tT able , then H 0 is rejected and H a is accepted. It can be concluded that the Everyone Is Teacher Here method has an effect on speaking skills in the Indonesian language subject of fifth grade students at SD Negeri 03 Aur Tajungkang. Keywords: Everyone Is Teacher Here Method , Speaking Skills